Why skills builders matter: understanding the motivations behind course-taking among a focused subsection of noncompleters at a California community college - Allan-Bentley, Beth (Kansas State University, 2021)
Skills builders take courses at the community college to gain skills and often exit without completing a degree or certificate. Although the college categorizes them as noncompleters, skills builders believe they have met their educational goals. The purpose of this explanatory sequential mixed-method study was to explore skills builders’ motivations for succeeding in courses taken at a community college and the relevance of those courses to their educational goals and job opportunities. The study addressed three primary research questions: What beliefs contributed to skills builders’ success in community college courses? How relevant were completed courses to skills builders’ educational goals? How relevant were completed courses to skills builders’ job opportunities? Using the expectancy-value theory (EVT) of motivation, the research results support the notion that skills builders were motivated to take courses to hone or learn new skills because of their enjoyment and interest in acquiring new competencies. This focus most closely matches the interest subtheme from the value side of EVT. Although other factors may influence motivation, and the results did have some slight variation by subgroups, overall, skills builders value being lifelong learners, gathering knowledge from experts in the field, and using it to grow in their life and career. It is not about a degree or certificate completion. Therefore, community colleges can look to change how they measure success for this segment and work with the business community to provide future skills training.
Keywords: Skills builders; Career technical education (CTE); Community college; Expectancy-value theory of motivation; Noncompleters; Educational goals